Practical and Ethical Aspects of Advance Research Directives for Research on Healthy Aging: German and Israeli Professionals’ Perspectives - Werner, Perla; Schicktanz, Silke (Frontiers in Medicine, 2018)
Background: Healthy aging is the development and maintenance of optimal cognitive, social and physical well-being and function in older adults. Preventing or minimizing disease is one of the main ways of achieving healthy aging. Dementia is one of the most prevalent and life-changing diseases of old age. Thus, dementia prevention research is defined as one of the main priorities worldwide. However, conducting research with persons who lack the capacity to give consent is a major ethical issue. Objective: Our study attempts to explore if and how Advance Research Directives may be used as a future tool to deal with the ethical and practical issues in dementia research. Method: We conducted focus groups and in-depth interviews with German and Israeli professional stakeholders from the fields of gerontology, ethics, medical law, psychiatry, neurology and policy advice (n= 16), and analyzed the main topics discussed regarding cross-national similarities and controversies within the groups, as well as across the two national contexts. Results: While both countries are in the midst of a developmental process and have recognized the importance and need for ARD as a tool for expanding healthy aging, Germany is in a more advanced stage than Israel because of the EU regulation process, which indicates the influence of international harmonization on these research-related ethical issues. Consensual themes within the qualitative material were identified: the need for a broader debate on ARD, the ethical importance of autonomy and risk-benefit-assessment for ARD implementation, the role of the proxy and the need for the differentiation of types of dementia research. Controversies and dilemmas aroused around themes such as the current role of IRBs in each country, the need for limits, and how to guaranty safeguarding and control. Discussion: Implementing a new tool is a step-by-step procedure requiring a thorough understanding of the current state of knowledge as well as of the challenges and hurdles ahead. As long as improving quality of life and promoting autonomy continue to be core elements in the process of healthy aging, efforts to advance knowledge and solve dilemmas associated with the implementation of ARD is of the utmost importance